Flexible response of bamboo-epoxy frames. Issue 2 (3rd April 2017) - West, Roger P.; Bhalla, Suresh; Bhagat, Diwakar
Abstract: This paper describes some of the extensive outcomes of a structural load test on a full-scale bamboo-epoxy composite frame. A bundle of 30 small diameter thick-walled bamboo culms was bonded using an epoxy-fibre resin to form structural beam and column elements, which were connected at the beam/column joints using rebar and a novel composite glue to form a Portal frame. The frame was heavily instrumented with over 90 strain gauges to establish the locations of any delaminations or hinge formations during inelastic behaviour under load. The frame and the gauges were assembled in India and shipped to Ireland for testing. In Trinity College Dublin, the frame was supported by steel shoes bolted to a 3000 kN internal reaction rig, with additional passive lateral supports in case of out-of-plane instability during loading. This paper describes the load–displacement response under combined horizontal and vertical loading, together with an explanation of the frame's non-linear behaviour using the evidence provided by the strain gauges, including the development of significant secondary moments due to the frame's flexibility. The residual load capacity of the frame was evident whereupon significant inelastic deformations occurred as the actuator heads were allowed to continue to distort the frame under a sustained load.